New Realism and Contemporary Philosophy - Kroupa, Gregor; Simoniti, Jure (Bloomsbury Academic, 2020)
This open access book advances the current debate in continental realism. In the field of contemporary continental ontology, Speculative Realist thinkers are now grappling with the genealogy of their ideas in the history of modern philosophy. The Speculative Realism movement prompted a debate, criticizing the predominant postmodernist orientation in philosophy, which located its origins in Kantian "correlationism" which supposedly ended the period of early modern naive realist metaphysics by showing that the mind and the outside world can only ever be understood as correlates. The debate over a new kind of realism has attracted many supporters and critics. In order to refocus its specific interpretation of modern philosophy in general and of the Kantian gesture in particular, this volume brings together major authors working on contemporary ontology and historians of ideas. It underlines and illustrates the fact that contemporary continental philosophy is rediscovering its past in original ways by productively re-interpreting some of the key concepts of modern philosophy. The perspectives and accounts of the key concepts of the history of philosophy are different in the views of individual contributors, and sometimes radically so, yet the discussion between contemporary realists and their critics shows that the real battleground of new ideas lies not in developing the philosophical motifs of the end of the 20th century, but rather in rethinking the milestones of modern philosophy. The eBook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com.